2021
DOI: 10.2478/raon-2021-0039
|View full text |Cite
|
Sign up to set email alerts
|

The role of haematological parameters in predicting the response to radical chemoradiotherapy in patients with anal squamous cell cancer

Abstract: Background Historically, the treatment of choice for anal cancer had been abdominoperineal resection (APR). Radical radiotherapy with concurrent 5-fluorouracil plus mitomycin C chemotherapy was later established as standard therapy, although with a failure rate of 20–30%. The aim of this study was to evaluate the outcomes after radical chemoradiotherapy (CRT), prognostic and predictive factors and patterns of failure. Patients and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…The NMR has been investigated in low-risk differentiated thyroid carcinoma as a prognostic factor, and it was found that lower initial level is related to a worse prognosis, which is in relation to our findings ( Offi et al, 2021 ). Our group has previously shown that hematological parameters easily derived and routinely determined by low-cost and minimally invasive methods might be useful in predicting the response to chemoradiotherapy in patients with anal cancer ( Stojanovic-Rundic et al, 2021 ). Also, we successfully evaluated the role of hematological parameters in predicting the survival and toxicity to specific treatment in the lung cancer setting ( Jokic et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The NMR has been investigated in low-risk differentiated thyroid carcinoma as a prognostic factor, and it was found that lower initial level is related to a worse prognosis, which is in relation to our findings ( Offi et al, 2021 ). Our group has previously shown that hematological parameters easily derived and routinely determined by low-cost and minimally invasive methods might be useful in predicting the response to chemoradiotherapy in patients with anal cancer ( Stojanovic-Rundic et al, 2021 ). Also, we successfully evaluated the role of hematological parameters in predicting the survival and toxicity to specific treatment in the lung cancer setting ( Jokic et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our group has previously shown that hematological parameters easily derived and routinely determined by low-cost and minimally invasive methods might be useful in predicting the response to chemoradiotherapy in patients with anal cancer 7 . Also, we successfully evaluated the role of hematological parameters in predicting the survival and toxicity to specific treatment in the lung cancer setting 55 .…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of cases, it is diagnosed in advanced stages, when treatment options are limited. In this regard, in the past we have profiled the diagnostic, prognostic and predictive factors for cancers of the digestive system, leading to improved research strategies for patient management and care [2][3][4][5][6][7] . However, there is a need for better primary prevention, more effective screening program, diagnosis at an earlier stage of the disease and improvement of existing treatment modalities in our country and on a global level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Serbia in the majority of cases, CRC is diagnosed in advanced stages where limited treatment options are available and survival is poor. Our group and others have invested efforts into profiling the diagnostic, prognostic and predictive factors for CRC and anal cancer, in an effort to provide better research strategies for treatment and overall management (Jakovljevic et al, 2012a; Brotto et al, 2013; Cavic et al, 2016; Nikolic et al, 2021; Stojanovic-Rundic et al, 2021; Vuletić et al, 2021; Marinkovic et al, 2023; Stanojevic et al, 2023).…”
Section: Introductionmentioning
confidence: 99%